OntoDRE: An ontology for the requirements engineering decision process - Miranda, James William Pontes [UNESP]; Souza, Rogeria Cristiane Gratao de [UNESP]; Rocha, A.; Goncalves, R.; Penalvo, F. G.; Martins, J. (Ieee, 2021)
The decision-making process in the initial phase of software development is highlighted by the amount and importance of decisions and how these decisions can impact the entire development cycle and, consequently, the final results. Requirements Engineering (RE) is the sub-area of Software Engineering dedicated to establishing the rules, procedures, and metrics for an adequate understanding of the expectations involving software. In this context, this paper presents an application ontology for formalizing the decision-making process during the RE phase, aiming to provide mechanisms to assist the automation of this process and, consequently, to base the decisions to be taken. As a proof of concept, a case study was carried out to demonstrate the practical use of ontology for creating an application on the Semantic Web. The results attest to the applicability of the ontology, as well as its contribution to the RE decision-making process.
Keywords: Ontology; Requirements engineering; Semantic web; Decision-making